ANALISIS AKSESIBILITAS SISTEM INFORMASI REPOSITORI ARSIP DAN KEPUSTAKAAN TERHADAP REKAM JEJAK KEBIJAKAN PUBLIK DI PROVINSI DKI JAKARTA - Lusi Puspasari; Dyah Ayu Kusuma Dewandaru; Muhammad Ridwan; Wisnu Putri Airmas Jati; Rani Sabtelasari (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The transformation of digital governance in DKI Jakarta Province through the implementation of e-government has established a massive data infrastructure. Nevertheless, the proliferation of digital portals has not been matched by public accessibility in tracing the complete historical trajectory of public policy formulation. This study aims to analyze the accessibility level of the regional information repository ecosystem and identify the barriers to integration between archival and library systems. Employing a Systematic Literature Review (SLR) approach encompassing academic literature and government regulations from the past five years (2021–2026), this study reveals that the capital's digital ecosystem of data governance remains entrapped within bureaucratic silos. Legal repositories (JDIH), dynamic legislative and executive archives, and regional libraries operate in a highly fragmented manner. This lack of interoperability perpetuates a bureaucratic monopoly over historical data, culminating in profound information asymmetry and a disconnection of institutional memory between state administrators and the public. As a resolution to this structural deadlock, this article proposes a conceptual model utilizing a metadata crosswalk. System convergence through integrated metadata is crucial for reconstructing the trajectory of public policies from their initiation to legitimation phases, thereby enhancing the transparency of local governance and fostering an evidence-based policy research ecosystem